Threat to the Group's Image Can Motivate High Identifiers to Take Action Against In-group Transgressions. (November 2018) - Shuman, Eric; Johnson, Dan; Saguy, Tamar; Halperin, Eran
When transgressions are committed by a group, those highly identified with the group are often least likely to recognize the transgressions, feel collective guilt, and engage in action to address them. We hypothesized that especially among high identifiers, demonstrating that in-group transgressions threaten the group's image can induce normative conflict and thus collective guilt and action. In the first study, we demonstrate that high (vs. low) image threat increases normative conflict among high identifiers. In Study 2, we show that inducing normative conflict through image threat leads to increased collective guilt and collective action among high identifiers. In Study 3, we replicate this effect with the addition of a control condition to demonstrate increased normative conflict and collective guilt relative to both a low threat and baseline conditions. In Study 4, we again replicate these effects with a modified manipulation that more precisely manipulated image threat. Together, these studies indicate that image threat can be an effective motivator for high identifiers to address in-group transgressions.